Hybrid Cryptosystem with Computational Ghost Imaging Based on Integer Wavelet Transform and Chaotic Maps - Alnidawi, Khalid T.; Sagheer, Ali M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Computational ghost imaging encryption (CGIE) has gained increasing attention from researchers in the field of optical cryptography due to its unique phenomenon. However, traditional CGIE suffers from long imaging time, inherent system linearity, and an enormous number of random phase masks that must be transmitted as secret keys, which limits its application in practical communication. In this paper, a hybrid optical image encryption approach is proposed using CGIE based on integer wavelet transform and chaotic maps. In addition, Hadamard basis patterns are employed to reduce sampling times and improve reconstructed image quality. Simulation results demonstrate that the proposed system is robust against different types of attacks with high key sensitivity and low execution times of 0.03 s for encryption and 0.14 s for decryption. This approach will ensure broader adoption of this technology by facilitating its integration into cryptosystems.